(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The fast growth of cities in developing nations has put pressure on formal waste management institutions, which leave large service gaps that can be occupied by informal waste collectors. The paper investigates the socio-economic attributes, business environment, and significant factors that can affect the willingness of informal waste collectors to include themselves in the formal waste management systems. The study adopted a quantitative research design. 65 respondents took part in the study and descriptive statistics, Chi-square tests, and binary logistic regression were used to analyze the results. The results indicate that the knowledge of the formal waste management systems, perceived significance of integration, low income, and poor working conditions have a high impact on the willingness of collectors to integrate. Conversely, demographic variables such as gender and education level were not statistically significant predictors. The output of the logistic regression also shows that awareness is the most powerful predictor, which raises the chances of being integrated into formal systems significantly. The regression model has a moderate level of explanatory power and satisfactory predictive accuracy. These findings are important in highlighting the role of policy intervention strategies intended to strengthen awareness, working environments, and income support programs to informal waste collectors. These areas would be fortified, which may create more involvement in formal systems. Incorporation of informal waste collectors can enhance efficiency of operations, environmental sustainability as well as inclusive urban development. Therefore, the policymakers and other interested parties should identify and embrace the contribution of informal actors to the wider waste management process in order to bring in sustainable and fair city waste management.